(untitled) (Bangladesh Journal of Botany, 2010)
Eighteen taxa of the genus Jurinea Cass. growing naturally in Turkey were classified by numerical taxonomic analysis. Morphological and palynological characters of each individual were measured and quantified on the basis of 51 traits. Ten plants were chosen randomly for the measurements of metric characters related to the external morphology of the taxa and the average values used for statistical analysis via NTSYS-pc package. Standardized data were used to generate the dendrogram that revealed the phenetic relationships of the taxa. Geographic distribution pattern of the Jurinea species appear to be closely related to the Anatolian Diagonal. Key words: Numerical analyses; Jurinea; Asteraceae; Turkey DOI: 10.3329/bjb.v38i1.5118 Bangladesh J. Bot. 38(1): 47-53, 2009 (June)